Learning Strategies of Problem-Based Learning and Project-‎Based Learning on Students’ Programming Skills: A Bibliometric ‎Analysis and Systematic Literature Review - Rizki Muhamad‎ Sidik; Indra Gunawan; Isna Nurul‎ Haqiqi; Gevira Nur Harnika‎ (Digital Learning, Social Science, and Life-course Studies, 2025)
The increasing demand for programming logic skills in the era of digital transformation has driven this study to identify and analyze effective learning strategies for their development. This research focuses on the implementation of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) approaches, which are considered essential for enhancing problem-solving, analytical, and developmental processes in programming education. A Systematic Literature Review (SLR) combined with bibliometric analysis was employed to examine relevant studies published between 2020 and 2025. The PRISMA guidelines were applied to select the literature, and data sources were collected using the Publish or Perish (PoP) application. A total of 32 articles met the inclusion criteria and were subsequently analyzed using VOSviewer software to identify research trends, patterns of collaboration among researchers, and keyword co-occurrence networks. The findings indicate that PBL- and PjBL-based learning strategies are effective in improving students’ understanding of programming logic, particularly in enhancing creativity, problem-solving abilities, and critical thinking skills. These findings are expected to serve as a foundation for the development of curricula and instructional innovations in programming education that are more responsive to the demands of the digital era.